Toxicidad aguda del extracto etanólico de hojas de Clidemia hirta L. Don en Mus musculus Balb/C. - Encinas Pinto, Marcia (2025)
Objective: To determine the acute toxicity of Clidemia hirta L. Don (purple mullaca) leaves on Mus musculus Balb/C. Methodology: The dried leaves of C. hirta L. Don were macerated in 96° ethanol and then concentrated in a rotary evaporator. For the evaluation of acute toxicity, 03 experimental groups of 05 female mice were formed, where the plant extract was administered at doses of 25, 200 and 2000 mg/kg. Body weight, behavior and signs of toxicity were monitored; biochemical parameters, macroscopic and microscopic evaluation of organs. Results: Mortality in the three experimental groups was 0%; in the control it is mentioned that weight gain was minimal. Furthermore, weight loss was recorded in the three experimental groups (25, 200, and 2000 mg/kg). The weights of organs, liver, kidneys, brain, and heart, were similar to those of the control group, and the liver weight was lower at the 2000 mg/kg dose. Compared to the lungs of the control group, the mass was slightly greater. Biochemical values were within normal parameters, and only some vascular alterations were observed in histological sections. Conclusions: The lethal dose of the ethanolic extract of C. hirta was determined to be greater than 2000 mg/kg-1; therefore, the ethanolic extract of C. hirta is considered harmless.